Real‐world use, effectiveness and safety of anti‐viral treatment in chronic hepatitis C genotype 3 infection. Issue 5 (12th January 2017) - Cornberg, M.; Petersen, J.; Schober, A.; Mauss, S.; Böker, K. H. W.; Link, R.; Günther, R.; Serfert, Y.; Pfeiffer‐Vornkahl, H.; Manns, M. P.; Sarrazin, C.; Hüppe, D.; et al.
Summary: Background: Treatment of chronic hepatitis C genotype 3 (GT3) is more challenging compared with other genotypes. Since 2014, several new treatment regimens have been approved but sometimes based on limited data. Aim: To validate the use, effectiveness and safety of anti‐viral treatment in chronic hepatitis C genotype 3 infection under real‐word conditions. Methods: The German Hepatitis C‐Registry is a large national non‐interventional real‐world study for patients with chronic hepatitis C. A total of 1322 GT3 patients were enrolled (211 untreated and 1111 treated patients). Results: Between February 2014 and September 2015, five different treatment strategies have been used (PegIFN+RBV, PegIFN+RBV+SOF, SOF+RBV, DCV+SOF±RBV, LDV/SOF±RBV). Treatment uptake and use of treatment concepts changed markedly and rapidly during the study influenced by new approvals, guideline recommendations, and label updates. PegIFN‐based therapies constantly declined while DCV‐based therapies increased with one interruption after the approval of LDV/SOF, which was frequently used until new guidelines recommended not using this combination for GT3. Per‐protocol SVR ranged from 80.9% in the PegIFN+RBV group to 96.1% in PegIFN+RBV+SOF treated patients. Treatment‐experienced patients with cirrhosis showed a suboptimal SVR of 68% for SOF+RBV but a high SVR of 90–95% for DCV+SOF±RBV. The safety analysis showed more adverse events and a stronger decline of haemoglobin for RBV containing regimens. Conclusions: Real‐world data can validate the effectiveness and safety for treatment regimens that had previously been approved with limited data, in particular for specific subgroups of patients. The present study demonstrates how rapid new scientific data, new treatment guidelines, new drug approvals and label changes are implemented into routine clinical practice today. Abstract : Linked Content This article is linked to Bruno et al paper. To view this article visithttps://doi.org/10.1111/apt.14042 .